Field lab on internationalization - the case of missangas & co. in Finland - Gameiro, Maria Eduarda Costa (2024)
This document provides a detailed analysis of the internationalization process of Missangas&Co., a Portuguese bead-based jewelry SME, and aims to guide it towards sustainable growth in the global jewelry market. It begins with an assessment of the company's current operations, financials, and organization, along with an international market selection analysis from where a shortlist of 5 countries was derived, with Ireland being identified as the ideal target for expansion. The report further outlines a comprehensive plan for entering this market, encompassing marketing strategies and financial projections. Additionally, it features a literature review on International Entry Mode Selection to support the proposed strategies.